Memaknai Pendidikan Keluarga Katolik Ditinjau Dari Dokumen Familiaris Consortio - Gregorius Daru Wijoyoko; Nicolas Eka Novian Wicaksono; Paulina Nirmayazitha Pusparani (Universitas Maritim AMNI Semarang, 2023)
The focus of the discussion within this research is on understanding moral values in Catholic Family education. In the midst of a world that is shaken by various storms of decline in moral values, such as consumerism, individualism, and hedonism, this has made dangerous impact toward the education of Catholic families. The family, especially the Catholic family, has a role as well as a responsibility to provide direction so that every member in the Catholic family survives from various challenges and threats of moral decline. The Catholic Church, through the Apostolic Exhortation –Familiaris Consortio, has provided direction in the efforts of Christian families to maintain moral values. Familiaris Consortio should be the basis for education meaning by Catholic families so that the Sacrament of Marriage can be interpreted seriously and minimize Catholic marriages that fail in the middle of the journey. This study will be divided into four main discussions that can help Catholic families upgrading moral values in their role in educating. The four discussions are: The situation of the family in today's society, the rights and obligations of parents regarding education, educating in the essential values of human life, and the mission of Education and the Sacrament of Marriage.